PENEGAKAN HUKUM PIDANA TERHADAP TINDAK PIDANA PEMALSUAN DATA PERSONAL MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2011 TENTANG KEIMIGRASIAN - Duwi Purnama Sari (Fakultas Hukum Universitas Sriwijaya, 2021)
The criminal investigation of Immigration against foreign citizen who is intentionally provides invalid data in the form of falsify the personal data that is under the process in filling an application of Travel Document of The Republic of Indonesia occur at Palembang Class I Immigration office in 2018 by Ling Lee Tiong as known as Muslim. He has perpetrates violates Article 126C of Law of The Republic of Indonesia Number 6 of 2011 concerning Immigration. Under the process of law enforcement of Immigration, the determination of a violation case is solved with the criminal law or administrative is an authority of Immigration Officers (discretion). This study discusses about law enforcement and the barrier of law enforcement against the criminal act of falsify the personal data based on Law of The Republic of Indonesia Number 6 of 2011 concerning Immigration and policy for the future. This type of research used in this research is empirical juridical law. This research was conducted at Palembang State Court and Palembang Class I Immigration office. Criminal law enforcement against the criminal act of falsify the personal data based on Law of The Republic of Indonesia Number 6 of 2011 concerning Immigration at Palembang Class I Immigration office in the form of criminal law enforcement as set forth in laws and regulations (In Abstracto) and actual law enforcement (In Concreto). There are two (2) efforts on criminal law enforcement, namely preventive law effort and repressive law effort. The most dominant factors that hinder law enforcement are legal enforcement factor and facilities factor. The Policy for the future of criminal law shall still refer to the policy of criminal law formulated in the concept of Criminal Code.